Native-Speakerism in a Locally Developed Indonesian EFL Textbook: A Critical Discourse Study - Kirana, Satwika Nindya; Methitham, Phongsakorn (English Education Department, Universitas Islam Indonesia, 2022)
The objective of the study is to examine to what extent native- speakerism is embedded in an EFL textbook for senior high school students in Indonesia. Native-speakerism is an ideology that legitimates native speakers as superior models of English. The textbook was developed by local English teachers and supervised and published by the Indonesian Ministry of Education and Culture (Widiati et al., 2017). The study focuses on analyzing critical elements in the passages in the textbooks. Eighteen passages were analyzed qualitatively using a set of guideline questions developed from Fairclough (2001) three dimensions of discourse analysis. The findings show that native-speakerism is the second major ideology after Indonesia-center. It is embedded in four passages. Three passages contain native-speakerism that can be recognized on the sentence level. Another passage, disguised as Indonesia-center, transfers native-speakerism implicitly as it cannot be identified on the sentence level. The findings are presented descriptively with excerpts from the passages followed by an illustrated scenario for each excerpt. Suggestions on how to lessen native-speakerism transfer are presented in conclusion.